Transmission of disaster information in the implementation of relocation policies after the Earthquake, Tsunami and Liquefaction in Palu, Central Sulawesi - Bahri, Syamsul (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
Background: The handling of the major disaster that occurred in the city of Palu still leaves polemics, currently there are still people living in temporary housing who hope to receive proper compensation. There is no reason to turn away from the major disaster that occurred in the city of Palu. What is interesting is that even though it is given seriousness, it is known that the policy has reached a dead end in implementing the policy in the field, several polemics have not been resolved to date, so that the rehabilitation and reconstruction policy for affected residents has not gone according to plan as it should, the facts show that among those affected by the disaster, there are those who have lost their place. lived as a result of a disaster, whether his house was buried in the ground. due to liquefaction, it was washed away. clean due to strong tsunami waves or collapsed due to an earthquake on a powerful scale, found still screaming in refugee camps, they still live in the midst of uncertainty. Results: This research uses a qualitative research approach, paying attention to the information transmission section, by examining all important parts of the policies adopted and distributed to all stakeholders, especially the scope in correctly identifying all possibilities for the policies chosen, in the form of contradictions, agreements and deviations or differences. interpretation at the implementing level and the wider community, answering the extent to which the bureaucratic hierarchy provides strong support in implementing policies, the ability of stakeholders to define policies and capture important policy information. Conclusion: The shocking exposure regarding disaster management caused a lot of losses, gave rise to a lot of polemics, interpretations and policy choices that invited risk, handling disasters with new mechanisms that ignored conventional methods then gave rise to multiple interpretations, giving rise to debate, this then had an impact on the condition of the existing bureaucratic hierarchy as if -if they do not provide strong support in implementing the policy, this creates a deadlock in defining the relocation policy.